Pengaruh Operating Cash Flow dan Faktor Pendukung Lainnya terhadap Financial Distress - Violita Christy; Kartina Natalylova (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this research is to obtain empirical evidence about the effect of operating cash flow, liquidity, profitability, financial leverage, firm size, managerial ownership, institutional ownership, proportion of independent commissioners, and free cash flow on financial distress. This research used a sample of manufacturing companies that are consistently listed on Indonesia Stock Exchange ranged from year 2019 to 2021 as the population. The sample was obtained by using purposive sampling method and obtained final sample of 65 manufacturing companies listed on Indonesia Stock Exchange so as to obtain a total of 195 research data and used the multiple regression statistic. The result in this research showed that profitability and firm size had an effect on financial distress. A low profitability is a signal of company incapacity to convert revenue flow into profit, and so an increase on profitability will lower the probability of financial distress. Firm size had an effect on financial distress means the greater the company's total assets, the bigger probability the company to experience financial distress because of the greater expenses. Besides, operating cash flow, liquidity, financial leverage, managerial ownership, institutional ownership, proportion of independent commissioners, and free cash flow had no effect on financial distress.